2007
DOI: 10.1080/jom.2007.9710825
|View full text |Cite
|
Sign up to set email alerts
|

Drawing Maps and Remembering Landmarks after Driving in a Virtual Small Town Environment

Abstract: Participants were designated active drivers or passive passengers according to whether or not they had control over the displacements of a virtual vehicle, while taking 5, 10 or 15 tours of a virtual small town environment. When tested later, passive passengers were able to remember more landmarks than the active drivers. However, with successive tours, participants in both groups were able to draw better survey maps of the environment, though this effect was greater in passive passengers. Landmark memory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
3
5
0
Order By: Relevance
“…This is supported by previous studies reporting reduced recollection of learned words when attention was divided during encoding by a secondary task [35]. Furthermore, passive passengers were reported A u t h o r M a n u s c r i p t to recall more landmarks compared to active drivers [36]. Another possible cause for improved recognition rates for irrelevant landmarks, especially in the control group, might have been a response bias.…”
Section: Performancesupporting
confidence: 81%
“…This is supported by previous studies reporting reduced recollection of learned words when attention was divided during encoding by a secondary task [35]. Furthermore, passive passengers were reported A u t h o r M a n u s c r i p t to recall more landmarks compared to active drivers [36]. Another possible cause for improved recognition rates for irrelevant landmarks, especially in the control group, might have been a response bias.…”
Section: Performancesupporting
confidence: 81%
“…Three-dimensional virtual reality seems to stimulate memory due to higher body involvement but also reduced energy consumption [74]; however, Palermo and co-authors [79] found that immersive interaction with a gyroscope, although reported as interesting, could be frustrating and showed a minor degree of engagement compared to classic active interaction with a mouse. Finally, a trial effect emerged confirming the positive effect of repetition on performance (e.g., [59]). Interestingly, exposure times led to better survey representation for passive participants, as noted by Sandamas and Foreman [59].…”
Section: Resultssupporting
confidence: 57%
“…Graphic realism when building VEs should take into account the fact that a detailed environment positively affects memory performances [77]. Other elements that neuroscientists in the field of VR and memory should consider are the type of encoding (incidental vs. intentional); although the authors of [62] showed no effect of encoding, in our review intentional encoding leads to better performance across the populations and the type of memory assessed [8,9,43,58,59,67,68,69,70,75,80]. Crucially, only one study [72] compared active VR vs. passive VR vs. real-world navigation, with real-world navigation and active VR leading to better spatial recall, in this order, compared to passive VR.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations